Management of Turcicum leaf blight [Exserohilum turcicum (Pass.) Leonard & Suggs] of maize (Zea mays L.) through integration of host resistance and fungicide at Bako, western Ethiopia - Debela, M.; Dejene, M.; Mengesha, A. (Academic Journals, 2017)
Turcicum leaf blight (TLB) (Exserohilum turcicum) is a major disease affecting maize production in western Ethiopia. The objectives of this study were to determine the effect of maize varieties integrated with fungicides on epidemics of turcicum leaf blight; to determine the effect of turcicum leaf blight severity on yield and yield components of maize; and to assess the cost and benefit of using fungicides. The field experiment was conducted at Bako Agricultural Research Center in 2014 main cropping season using six maize varieties (BH-540, BH-543, BH-546, BH-660, BH-661 and AMHQ-760) integrated with foliar sprays of the systemic fungicide propiconazole (Tilt) at the rate of 350 ml ha-1 and the contact fungicide mancozeb (Dithane M-45) at 2.6 kg ha-1. The experiment was arranged in 3 × 6 factorial combinations in split plot design with three replications. A pinch of ground maize leaf infected by E. turcicum was inoculated at third-fifth leaves. Unsprayed plots were left as control or check for each variety. Disease severity was scored using 1 to 5 scale on 12 randomly-tagged plants in the central rows. Integration effects of varieties with fungicides significantly affected the grain yield and thousand kernel weight (TKW) of maize varieties. The highest (11383 kg ha-1) grain yield was obtained from propiconazole-treated hybrid maize variety BH-546. Turcicum leaf blight resulted in grain yield losses of up to 40.7% on the unsprayed plots of the susceptible variety BH-543. Percent severity index, AUDPC, incidence and disease progress rates were negatively correlated with yield components regardless of grain yield loss. The highest marginal benefit (ETB 48,801.28 ha-1) and marginal rate of return (ETB 6.33) were obtained from propiconazole-treated varieties BH-543 and BH-546, respectively. This study contributes to integrated TLB management options, and to make a valid recommendation for TLB management strategy, the study should be repeated over years and locations where TLB of maize is of major economic importance.